Quality of life of alcohol-dependent adults - Klavdija Čuček Trifkovič; Blanka Kores Plesničar; Alenka Kobolt; Margaret Denny; Suzanne Denieffe; Leona Cilar (Nurses and Midwives Association of Slovenia, 2020)
Introduction: Alcohol dependence is the most prevalent addiction disorder that develops gradually as an interplay of individual and social factors. It impacts the quality of life of affected individuals. The purpose of this study was to examine the quality of life of alcohol-dependent people at different stages of treatment compared to individuals without alcohol dependence. Methods: A mixed-methods study was conducted. First, a cross-sectional study (n = 502) was conducted using a validated Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q). Focus groups for subjective quality of life assessment were also conducted. Data were analysed using descriptive and inference methods (Mann Whitney U Test) with the SPSS, version 20 programme. Results: Non-dependent participants are significantly more satisfied with each of the quality of life  component than alcohol-dependent participants. Differences were demonstrated in a sense of well-being and leisure-time activities. Differences between alcohol-dependent and non-dependent participants were seen in the domains of physical health, work satisfaction and social relationships. Discussion and conclusion: Alcohol-dependent participants reported a lower quality of life than non-alcohol dependent participants as alcohol dependents confront numerous problems associated with their dependence. There is a need for further research in the field of alcohol dependence in relation to the quality of life.